Ovicidal and Larvicidal Effects of Garlic and Asafoetida Essential Oils Against West Nile Virus Vectors. Issue 2 (12th April 2018) - Muturi, Ephantus J; Ramirez, Jose L; Zilkowski, Bruce; Flor-Weiler, Lina B; Rooney, Alejandro P
Abstract: We examined the chemical composition of garlic and asafoetida essential oils and their individual and combined toxicity against larvae of Culex pipiens Linnaeus and Culex restuans Theobald (Diptera: Culicidae). The effect of the two essential oils on egg hatch was also examined. Ten and 12 compounds, respectively, were identified in garlic and asafoetida essential oils. Allyl disulfide (49.13%) and diallyl trisulfide (31.08%) were the most abundant compounds in garlic essential oil accounting for 80.2% of the total oil. In contrast, (E)-sec-butyl propenyl disulfide (30.03%), (Z)-sec-butyl propenyl disulfide (24.32%), and disulfide, methyl 1-(methylthio)propyl (21.87%) were the most abundant compounds in asafoetida essential oil. Allyl disulfide accounted for 7.38% of the total oil in asafoetida essential oil and was one of only three compounds found in both oils. For both mosquito species, garlic essential oil was more toxic than asafoetida essential oil with Cx. restuans (LC50 : garlic = 2.7 ppm; asafoetida = 10.1 ppm) being more sensitive than Cx. pipiens (LC50 : garlic = 7.5 ppm; asafoetida = 13.5 ppm). When combined, the two essential oils had antagonistic effects. The majority of Culex egg rafts exposed to garlic (73.1%) or asafoetida (55.8%) essential oils failed to hatch and larvae of the few that did hatch mostly died as first instars. Allyl disulfide exhibited strong ovicidal and larvicidal activity suggesting its important contribution to the overall toxicity of the two essential oils. Thus, garlic and asafoetida essential oils are potent mosquito ovicides and larvicides but if used jointly, they could undermine vector control programs.